Extreme sensitivity of plasmon drag to surface modification. (28th October 2020) - Ronurpraful, T; Jerop, N; Koech, A; Thompson, K; Noginova, N
Abstract: Giant enhancement of photocurrents in plasmonic structures (plasmon drag effect) provides opportunities for compact electric monitoring of plasmonic effects, and thus is promising for plasmonic-based sensing applications. In the experiment, we measure photoinduced electric signals in flat and profile-modulated systems, and test their sensitivity to small changes of the local dielectric environment, such as a presence of Langmuir–Blodgett monolayers at the metal surface. We show that the addition of a stearic acid monolayer leading to a small shift in plasmon resonance conditions can be ultimately resolved with electrical measurements as the switching in the photovoltage polarity.